An electrospray ionisation apparatus for gas phase study of biomolecules. Issue 24 (January 2020) - Chiarinelli, J; Bolognesi, P; Ramillon, J M; Rousseau, P; Domaracka, A; Castrovilli, M C; Avaldi, L
Synopsis: A set-up to study large biomolecules in the gas phase based on an ElectroSpray Ionisation source has been installed at CNR-ISM in Rome, and it is currently under commissioning. Accurate ion optics simulation provide crucial feedback in the understanding and optimisation of its performance.